Employment expectations and uncertainties ahead of the new German minimum wage - Bossler, Mario (Nürnberg, 2016)
"Followed by an extensive policy discussion late 2013 and early 2014, the new German minimum wage was introduced on 1 January 2015. This article analyzes announcement effects of the new statutory minimum wage on employer expectations in 2014. The IAB Establishment Panel allows for a difference-in-differences comparison between affected and unaffected employers and entails variables that address the employers' employment expectations. In 2014, affected employers show an increased employment uncertainty and a drop in their expected employment development. They also more likely report wage costs to become a problem. In size, the employment expectations translate into a loss of about 12 800 jobs."